1984
DOI: 10.1007/bf00127294
|View full text |Cite
|
Sign up to set email alerts
|

Retention of methanogens in colonised reticulated polyurethane foam biomass support particle

Abstract: Methanogens colonised on reticulated polyurethane foam BSP rapidly lost biomass raven exposed to hydrodynamic stress.The loss was independent of the porosity of the BSP matrix.These findings indicate the binding forces between methanogen and particle surface is weak and may impose a limit on the potential for process intensification in fixed or fluidised bed methane digesters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
7

Year Published

1984
1984
2005
2005

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 11 publications
0
7
1
7
Order By: Relevance
“…Gijzen et al (1988) reported on the adherence of methanogenic archaea to polyurethane foam matrices from a reactor treating organic acids as well. These results contradict Fynn and Whitmore's (1984) findings on the adherence of enriched methanogenic culture to polyurethane foam. According to these authors, this adhesion was weak, making removal of the biomass from the support relatively easy.…”
Section: Resultscontrasting
confidence: 98%
“…Gijzen et al (1988) reported on the adherence of methanogenic archaea to polyurethane foam matrices from a reactor treating organic acids as well. These results contradict Fynn and Whitmore's (1984) findings on the adherence of enriched methanogenic culture to polyurethane foam. According to these authors, this adhesion was weak, making removal of the biomass from the support relatively easy.…”
Section: Resultscontrasting
confidence: 98%
“…In this sense, the support utilized to immobilize the biomass plays an essential role in these systems, and is directly associated with the cellular retention time, biomass concentration and microbial diversity. Polyurethane foam, which has been studied for many years for the adhesion of anaerobic microorganisms, has shown promising results (Huysman et al, 1983, Fynn andWhitmore, 1984;Calzada et al, 1984;Gijzen et al, 1988;Pascik, 1990;Varesche et al, 1997;Picanço et al, 2001;Ribeiro et al, 2003). However, although this support material provides a suitable environment for the adhesion of a mixed consortium of anaerobic microorganisms, its application in fullscale fixed-bed reactors must be carefully investigated, since it is a compressible material and the accumulation of solids or polymeric substances in the interstices of the bed can seriously impair the flow pattern in the reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Como suporte para imobilização da biomassa anaeróbia, utilizou-se preferencialmente espuma de poliuretano, material utilizado com sucesso anteriormente por pesquisadores em processos anaeróbios, principalmente na década de 1980 (Huysman et al, 1983;Fynn & Whitmore, 1984;Calzada et al, 1984;Gijzen et al, 1988;Pascik, 1990 Os dados obtidos puderam, então, ser usados para geração de modelos e estabelecimento de bases racionais para aumento de escala e projeto.…”
Section: Considerações Iniciaisunclassified
“…Huysman et al (1983), embora tenham considerado a espuma de poliuretano uma excelente matriz para colonização de organismos metanogênicos, acreditavam que a biomassa metanogênica estava apenas retida mecanicamente na forma de micro colônias dentro dos poros do material. Fynn & Whitmore (1984) observaram que velocidades superficiais de líquido menores que 1,5…”
Section: A Configuração Do Reator Anaeróbio Horizontal De Leito Fixounclassified
See 1 more Smart Citation